A Systematic Review: Associated Factor and Intervention Strategy of Stunting in South Sulawesi Province - Samintang Samintang; Harpiani Hasdar; Adhiyaksa Prananda RS; Usman Usman; Muh. Jusliandi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
South Sulawesi is a province with a high prevalence of stunting, which is around 30.5%. Various at- tempts have been made by the government to overcome the problem of stunting through various poli- cies and regulations as well as through a number of interventions. This paper aims to describe the policies and factors that cause the high incidence of stunting in the South Sulawesi region. The Pro- vincial Government of South Sulawesi has made efforts to formulate various regulations and pro- grams in the form of interventions, both specific and sensitive. Specific interventions are carried out by the health sector by focusing on the First 1000 Days of Life (HPK) program, while sensitive inter- ventions include providing access to clean water and sanitation. Apart from health, socio-economic factors are also known to have an effect on stunting, such as problems with poverty, education levels, and family income. Stunting prevention requires cross-sector cooperation and is carried out in an in- tegrated manner. The policies and regulations that exist at the central level must also be followed up with follow-up actions at the local level up to the village level and involve not only the health sector but also other related sectors. Community-based response systems involving other stakeholders need to be improved, because the high awareness of the community on the importance of balanced nutri- tion, pre-marital education, parenting, sanitation and environmental hygiene are a series of efforts to reduce stunting rates in South Sulawesi.